Nursing experience based on integrated Traditional Chinese and western medicine for a case of grade II phlebitis (1例II级静脉炎患者的中西医结合护理体会) - LI Jinhuan (李金环); YIN Kexin (尹可欣); E Haiyan (鄂海燕); WANG Xiaojia (王晓嘉); DUAN Yixuan (段怡璇); LIU Hongyan (刘红艳); XING Hui (兴慧) (中西医结合护理)
Patients are highly vulnerable to phlebitis induced by drug extravasation during intravenous injection of Iron sucrose. This paper summarized a nursing experience of a case of grade II phlebitis treated by nursing intervention of integrated traditional Chinese and western medicine. Nursing staff worked out a targeted nursing plan of integrated traditional Chinese and western medicine for patients, strengthened the nursing care of patients with grade II phlebitis pain, and gave full play to the advantages of traditional Chinese medicine. In addition to routine nursing, they cooperated with Ruyi Jinhuang Ointment, Kanghuier Absorption Patch and potato chips for joint application. Results Through the application of integrated traditional Chinese and western medicine nursing intervention, the pain of patients was alleviated, the repair process was accelerated, and the medical cost was saved. (蔗糖铁注射液用药过程中极易引发药物外渗致静脉炎。本文总结1例II级静脉炎患者中西医结合护理体会。护理人员为患者制定针对性的中西医结合护理方案, 加强II级静脉炎疼痛的护理, 发挥中医优势, 在常规护理的同时, 配合如意金黄膏、康惠尔吸收贴及土豆片联合分段贴敷治疗。通过中西医结合护理分段干预贴敷治疗, 减轻患者痛苦, 加快修复进程, 节约医疗成本。)